Pengaruh Pengembangan Karir dan Komitmen Kerja Terhadap Kinerja Karyawan di Grand Asrilia Hotel Bandung - Darul Wiyono (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
The purpose of this study was to determine the effect of both partial and simultaneous career development and work commitment on employee performance at Grand Asrilia Hotel Bandung. The method used in this research is quantitative with a descriptive and verification approach. The sample used is 77 respondents, the data obtained through probability sampling technique by providing a questionnaire containing 39 statements/questions. The data analysis technique used multiple linear analysis with the help of the IBM SPSS 23.0 program. The results obtained either partially or simultaneously that career development and performance commitment have a positive and significant effect on employee performance at Grand Asrilia Hotel Bandung